Hepatitis C Cure with Antiviral Therapy – Benefits beyond the Liver. Issue 1 (January 2016) - Soriano, Vincent; Labarga, Pablo; Fernandez-Montero, José V; de Mendoza, Carmen; Esposito, Isabella; Benítez-Gutiérrez, Laura; Barreiro, Pablo
Liver disease is the major complication of chronic HCV infection. However, extrahepatic complications are common (50–75%), including mixed cryoglobulinaemia and B-cell lymphomas. Given that chronic hepatitis C has become curable using expensive oral direct-acting antivirals (DAAs), it seems worth revisiting the whole spectrum and burden of disease in HCV carriers. Herein, we update the most clinically significant medical complications associated with chronic hepatitis C and the evidence of benefits that would derive from a wide use of curative DAA therapies. Chronic HCV infection is associated with a broad spectrum of clinical conditions, including distinct rheumatic disorders (polyarthritis, sicca syndrome), lymphoproliferative conditions (mixed cryoglobulinaemia, monoclonal gammapathies and B-cell lymphomas) and damage at other organs due to persistent systemic inflammation, leading to renal, bone, neurological and/or cardiovascular disease. Eradication of HCV with DAAs is associated with amelioration and/or resolution of most liver-related and extrahepatic complications. Ultimately, gains in quality of life and survival favour treating everyone with hepatitis C regardless of liver fibrosis stage.